Outcome of In-Vitro Fertilization in the First Government Set-up Fertility Center of Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Infertility as a global health issue is very much attended by the health sectors of most of the developed countries of the world. It remains as a neglected issue in Bangladesh’s reproductive health policy as emphasis is always been on the problem of overpopulation. Bangladesh Armed Forces have come forward to establish the first government set-up Artificial Reproductive Technology (ART) center to help the infertile couples of Bangladesh.Aim: To assess the outcome of in-vitro fertilization (IVF) procedures in relation to different demographic characteristics of the patients getting treatment at Fertility center, combined military hospital (CMH), Dhaka.Methods: Out of more than thousand patients, 46 couples were selected for IVF cycle scheduled to be held on the month of July 2017 and October 2017. Each selected female and male patient had a normal basic fertility work up. In both batches, female factors were predominant. Male factor and combined factors were also present. Data were collected prospectively using a data collection sheet over the period of one year starting from July 2017 to June 2018 to observe the last patient upto the delivery of her offspring.Results: A total of 46 couples or 92 patients were treated for infertility. Out of 46 female patients, most (about 40%) were within the range of 26 to 30 years of age. About two-thirds patients had primary subfertility. Most common cause of infertility of female partners was the tubal cause (52%) and of male partners was severe oligozoospermia (47%). A procedure of IVF like conventional IVF was done in 64% and Intra Cytoplasmic Sperm Injection (ICSI) in the remaining. Embryo transfer was performed in 30 patients. The embryos of 13 (33%) patients were cryopreserved in both batches. Rate of retrieved oocytes ranged from 3 to 29 in the 1st batch and for the 2nd batch it was from 1 to 17. Pregnancy rate was 80% in first batch, but in the second batch it was only 33%. Abortion rate was also very high (80%) in the second batch.Conclusion: In fact, infertility has become a burning health issue to the sufferers of fertility problems as well as career-oriented generation of this century and the society seeks the remedy to help them. Like the Fertility Center, CMH, Dhaka other government set up centers should come up to provide facilities that enables the women having the dream of motherhood true.JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 29-34